O acesso da população negra à graduação da UFG: um estudo sobre a Lei 12.711/2012 - Pacheco, Jakeline de Andrade (2021)
The essay circumscribes aspects of the Research Line “State, Policies and History of Education”, of the Graduate Program in Education, in the Faculty of Education - Federal University of Goiás (UFG). This study designates as a broad objective to know the repercussions of the Law nº 12.711/2012 regarding the inclusion of black people in the most competitive careers at UFG, in each of the major areas of the Brazilian National Council for Scientific and Technological Development (CNPq). As specific objectives: discuss the myth of racial democracy in Brazil; discuss the process of miscegenation in the country; present the process of adherence to affirmative actions by Higher Education Institutions in Brazil (IES); portray the academic profile of students in terms of skin color and race, seeking to examine the trajectory of black quota students regarding performance, fulfillment, and permanence in the University. As for the methodological aspects, qualitative and quantitative approaches (quali-quantitative) were used, since it seeks to express a quantitative relationship, but also to compose an object plus results broad analysis of the UFG research case study. As for the theoretical foundations, the following mainly authors and essays were used to assist in the study analysis: Kabengele Munanga, Nilma Lino Gomes, Jessé de Souza (A elite do atraso), Florestan Fernandes, Thomas Skidmore (Preto no Branco), Silvio Almeida in contrast with the studies of Gilberto Freyre in the book “Casa Grande e Senzala” (1933). This work pursues to be relevant according to academic and social perspectives, as it sheds light on certain issues that were denied for a long time, which, as a matter of fact, made it impossible to create strategies for their solving and overcoming, since the existence of these problems was not even recognized. Thus, this dissertation contributes to the evaluation of an affirmative action public policy, the Law nº 12.711/2012, through a diagnosis regarded to access of the black population to UFG's high competition careers, hence building a series of important indicators that the Institution can evaluate and use for their decision making. In the first part of the study, the myth of racial democracy in Brazil will be addressed; in the second part, affirmative actions and their repercussions on Higher Education; and, finally, a historical and Institutional contextualization of the UFG is presented, about the implementation of affirmative actions and the Quota Policy (Law nº 12,711/2012). Considering the developed analysis, it will be concluded that the previously mentioned Law contributed to the access of students from public schools, and also to the access of black people to the analyzed careers. Since, before this, the occupation of spots by students of this profile was low or even non-existent during the period of 2010 to 2012. This fact contributes to the support of the thesis that the Quota Law was and is being of great importance for the access of black and "pardo" students to the high-demand careers at UFG. However, this access – when compared to the size of the black population and its educational deficit in Higher Education – can still be considered not very expressive on a regional scale. Given the timidness expressed by the inclusion of this group in the UFG, it is detected a need for renewing and continuing the Law nº 12.711/2012, besides the adoption of other actions that contribute to the decrease of racial inequalities, such as the access of black people to socially privileged places.